2022
DOI: 10.1371/journal.pone.0262692
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bacterial vaginosis and aerobic vaginitis and their associated risk factors among pregnant women from northern Ethiopia: A cross-sectional study

Abstract: This study aimed to determine the prevalence of bacterial vaginosis (BV) and aerobic vaginitis (AV) and their associated risk factors among pregnant women from Ethiopia. Also, this study investigated the bacterial pathogens and their antibiotic resistance in AV cases. A total of 422 pregnant women from northern Ethiopia were participated in this study. Socio-demographic and clinical data were recorded. Vaginal swabs were collected and used for wet mount and Gram stain methods to evaluate the AV and BV scores a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 72 publications
3
8
4
2
Order By: Relevance
“…In contrast to the present study, other reports found that history of recurrent infection, people how lived on the rural area, educational levels and women aged more than 45 years had significant associated with the infection rate (Geng et al, 2016;Kamga et al, 2019;Yalew et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the present study, other reports found that history of recurrent infection, people how lived on the rural area, educational levels and women aged more than 45 years had significant associated with the infection rate (Geng et al, 2016;Kamga et al, 2019;Yalew et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…However, the infection rate in such the report performed in Cameron (26.2%) (Kamga et al, 2019), Nepal (24.4%) (Ranjit et al, 2018), India (24%) (Modak et al, 2011). However, the infection rate in such different countries; India (19.6%) (Gupta et al, 2016), Brazil (20.7%) (Gondo et al, 2010), Nigeria (17.3%) (Ibrahim et al, 2014) and Ethiopia (20.1%) (Yalew et al, 2022). This discrepancy could be due to random sample variation, population size, analysis methods, distribution of geographical area, differences in the socioeconomic and behavioural among studied population.…”
Section: Discussionmentioning
confidence: 95%
“…As both Nugent's scores and Amsel's criteria have inherent limitations, DNA-based assays targeting BV are reproducible and may be used to diagnose difficult cases [28] . A lower BV prevalence was reported in an Ethiopian study, in which BV was diagnosed using Nugent's score in 20.1% of the patients [29] . The prevalence in other African countries was reported to be also lower; in a meta-analysis, the prevalence of BV in sub-Saharan Africa was 42.1% [30] .…”
Section: Discussionmentioning
confidence: 56%
“…(3-33,3%), Acinetobacter spp. (6,8%) [6][7][8][9][10]. Полімікробний фактор виникнення НВ та здатність бактерій виробляти резистентність до різних лікувальних речовин не дають змогу стандартизувати лікування, особливо для АВ, що і призводить до високої частоти рецидивів НВ в перший рік після терапії і складає від 30% до 70% [11,12,13] Критерії невключення у дослідження: жінки, хворі на НВ, молодше 18 та старше 49 років; жінки, хворі на НВ кандидозної або трихомонозної етіології; наявність в анамнезі операцій на статевих або органах гіпоталамо-гіпофізарно-надниркової системи; наявність об'ємних новоутворень жіночих статевих органів; наявність захворювань гіпоталамо-гіпофізарно-надниркової системи; наявність суб-і декомпенсованих супутніх захворювань; наявність онкохвороби; наявність цукрового діабету; наявність хвороб обміну речовин; наявність аутоімунних захворювань.…”
Section: вступunclassified